Effect of stable climate on milk content and technological properties of bulk tank samples in Czech Pied Cattle - Falta, Daniel; Polák, Ondřej; Chládek, Gustav (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2011)
The aim of this research was to investigate the effect of stable climate on milk content and technological properties of bulk tank milk samples. It was analysed 29 weeks’ samples on private farm in Říčany (3.6. – 16. 12. 2010). Milk originates from approx. 720 Czech Pied Cattle cows with average 7.500 kg/lactation. One day before taking samples average daily temperature and relative humidity were recorded. The bulk tank samples were analysed for average values of fat content (%), protein content (%), lactose (%), SNF – solids non fat (%), TA - titratable acidity (Soxhlet Henkel), RCT - rennet coagulation time (s) and quality of curd (class 1–5).It was found that the minimal and maximal daily temperature resp. relative humidity changed in range -7.4–26.2 °C resp. 53.7–98.9 %. It means that in particular periods dairy cows were exposed to heat stress. In mentioned periods (when temperature was close to 26 °C) lower protein and fat content of milk was found and worse curd quality was frequently experienced although RCT was longer in colder period. Close correlation was confirmed between stable temperature and protein, fat resp. SNF content (r = -0.88, -0,85 resp. -0.84; P < 0.01). Correlation coefficients of stable relative humidity with other parameters were contrary to those of stable temperature. Correlation between stable temperature and relative humidity was r = -0.66 (P < 0.01). Other parameters were not affected by stable temperature or humidity.